Pacing and stroke kinematics in 200-m kayak racing - Pickett, C. W.; Abbiss, C.; Zois, J.; Blazevich, A. J. (Journal of Sports Sciences, 2021)
Pacing profiles of 19 elite and sub-elite 200-m kayak athletes were examined through stroke-by-stroke analysis, using GPS/accelerometer methodology. Stroke rates and lengths were also quantified across multiple race segments. Whilst athletes reached peak velocity at between 40 and 60 m, it was not possible to determine specifically whether an all-out or positive strategy was employed. Race times were strongly and negatively correlated with the acceleration over the first ~25% of race distance (r = -0.95 ± 0.04) as well as average velocity over the first 30 m of the race (r>-0.9), i.e. faster starts were associated with faster finishing times. Furthermore, the maintenance of velocity, stroke rate and stroke length after reaching their maxima were strongly associated with race times. Stroke rates were higher (Cohen`s d = 5.19) in the elite than sub-elite athletes (group categorisation based on race times), but there were no substantial differences in stroke rates between athletes within the elite cohort. Nonetheless, longer stroke lengths were associated with faster race times within the elite cohort (r = -0.48 to -0.85). The current study suggests that faster rates of acceleration and the ability to exhibit greater stroke lengths at relatively high stroke rates are determinants of 200-m kayak race performance.